2021
DOI: 10.1186/s12891-021-04524-x
|View full text |Cite
|
Sign up to set email alerts
|

The 30-s chair stand test can be a useful tool for screening sarcopenia in elderly Japanese participants

Abstract: Background Low muscle strength has been focused on as an essential characteristic of sarcopenia, and the 30-s chair stand test (CS-30) could be a particularly useful test for assessing muscle strength. While it is speculated to be a beneficial tool for the assessment of sarcopenia, this remains to be verified. In this study, we examined the reliability and optimal diagnostic score of the CS-30 for assessing sarcopenia in elderly Japanese participants. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The predictive validity of performance tests adds to their utility as baseline and outcome measures in clinical research. For example, the 30-s sit to stand test was useful in distinguishing older persons with and without sarcopenia in one study [ 32 ]. In a study of persons with lower extremity osteoarthritis, those with timed up and go ​> ​13.5 ​s were twice as likely to report a fall in the prior year as those with timed up and go ​< ​13.5 ​s (58% vs. 31%, p ​= ​0.003) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The predictive validity of performance tests adds to their utility as baseline and outcome measures in clinical research. For example, the 30-s sit to stand test was useful in distinguishing older persons with and without sarcopenia in one study [ 32 ]. In a study of persons with lower extremity osteoarthritis, those with timed up and go ​> ​13.5 ​s were twice as likely to report a fall in the prior year as those with timed up and go ​< ​13.5 ​s (58% vs. 31%, p ​= ​0.003) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…100 In a more recent cross-sectional study involving 678 Japanese older adults (mean age: 74.7 ± 7.2 years), the 30 s CST had a sensitivity of 75.0-76.4% and specificity of 71.7-76.8% for diagnosing sarcopenia, using 17 and 15 stands as cut-offs for males and females, respectively. 101 Based on these findings, a cross-sectional study concluded that sit-to-stand tests better represent the physical performance compared with muscle strength, the 30 s CST may be a suitable alternative to the 5-time CST. 102 To measure impairments in IADLs, most RCTs in Asia have utilized a five-item questionnaire assessing the ability of community-dwelling older adults to (1) walk two to three blocks outdoors on level ground, (2) climb 10 steps without resting, (3) prepare own meals, (4) do heavy housework like scrubbing floors or washing windows, and (5) shop for groceries or clothes.…”
Section: Outcomes and Assessmentsmentioning
confidence: 96%
“…Apart from a chair, the CST does not necessitate any advanced apparatus or wide space to accomplish and has been shown to have a sensitivity of 75% and specificity of 94% for predicting low gait speed 100 . In a more recent cross‐sectional study involving 678 Japanese older adults (mean age: 74.7 ± 7.2 years), the 30 s CST had a sensitivity of 75.0–76.4% and specificity of 71.7–76.8% for diagnosing sarcopenia, using 17 and 15 stands as cut‐offs for males and females, respectively 101 . Based on these findings, a cross‐sectional study concluded that sit‐to‐stand tests better represent the physical performance compared with muscle strength, the 30 s CST may be a suitable alternative to the 5‐time CST 102 …”
Section: Outcomes and Assessmentsmentioning
confidence: 99%
“… 41 , 42 ) Both handgrip strength and chair stand tests are also recommended in sarcopenia screening with the same cutoff for diagnosis—handgrip strength of men <28 kg and women <18 kg; chair stand test of >10 seconds (5-time, ending with standing position) and >11 seconds (5-time, ending with sitting position), or men ≤17 and women ≤15 (30 seconds). 19 , 28 , 29 ) In addition, the gait speed test and TUG can be used as screening tools using the cutoff values of a gait speed of <1.0 m/s and TUG ≥12 seconds. 19 , 43 ) In clinical settings with a high prevalence of sarcopenia, adopting handgrip strength, chair stand test, gait speed, or TUG test may simplify the diagnostic steps for sarcopenia.…”
Section: Screening Testsmentioning
confidence: 99%